Evaluation of the Best Region for Measuring Eye Temperature in Dairy Cows Exposed to Heat Stress - Shu, Hang; Li, Yongfeng; Fang, Tingting; Xing, Mingjie; Sun, Fuyu; Chen, Xiaoyang; Bindelle, Jérôme; Wang, Wensheng; Guo, Leifeng (Frontiers in Veterinary Science, 2022)
Eye temperature (ET) has long been used for predicting or indicating heat strain in dairy cows. However, the region of interest (ROI) and temperature parameter of the eye have not been standardized and various options were adopted by previous studies. The aim of this study was to determine the best ROI for measuring ET as the predictor of heat strain in dairy cows in consideration of repeatability and validity. The ET of 40 lactating Holstein dairy cows was measured using infrared thermography. The mean and maximum temperature of five ROIs: medial canthus (MC), lateral canthus, eyeball, whole eye (WE), and lacrimal sac (LS), were manually captured. The results show that the ET of left eyes was slightly higher than that of right eyes. The ET taken in MC, WE, and LS within 2 min had a moderate to substantial repeatability. The maximum temperature obtained at the LS had the highest correlation coefficients with respiration rate and core body temperature (all P < 0.001). Therefore, the maximum temperature of LS should be considered by future studies that want to use ET as the predictor or indicator of heat strain in dairy cows.